TEACHING ENGLISH LANGUAGE TO THE BEGINNERS - Sada, Clary; Wiranto, Irfan Agung (Jurnal Visi Ilmu Pendidikan, 2024)
his   study   aims   to   find   out   the   appropriate   method   to   teach English   to   the   beginners.   Also,   the   finding   of   this   research   is   for publication in the journal. This study is conducted by using online qualitative   survey   technique.   The   subjects   of   this   study   were teachers   who   teach   English   for   beginners   in   Pontianak   and   its surrounding.   The   data   were   collected   by   a   set   of   close-ended statements in an online questionnaire and also an online interview. The   findings   showed   that   there   were   various   methods   that   can   be applied   in   teaching   English   to   the   beginners,   and   those   methods depend   on   the   students"™   learning   style.   Since   students"™   learning style are different from one to another, the teachers may use various methods   in   their   classroom.   However,   even   when   the   methods   are various,   not   every   method   is   effective   in   teaching   English   to   the beginners.   Therefore,   the   teachers   need   to   choose   the   appropriate methods carefully in teaching English to the beginners. Keywords:   Teaching   English,   Teaching   Beginners,   English Language Teaching